Altered static functional network connectivity predicts the efficacy of non-steroidal anti-inflammatory drugs in migraineurs without aura - Wei, Heng-Le; Yang, Wen-Juan; Zhou, Gang-Ping; Chen, Yu-Chen; Yu, Yu-Sheng; Yin, Xindao; Li, Junrong; Zhang, Hong (Frontiers in Molecular Neuroscience, 2022)
Brain networks have significant implications for understanding of migraine pathophysiology and prognosis. The aim of this study was to investigate whether large-scale networks dysfunction in patients with migraine without aura (MwoA) could predict the efficacy of non-steroidal anti-inflammatory drugs (NSAIDs). Seventy episodic MwoA patients and thirty-three healthy controls (HCs) were recruited. Patients were divided into MwoA with effective NSAIDs (M-eNSAIDs) and with ineffective NSAIDs (M-ieNSAIDs). Group-level independent component analysis and functional network connectivity (FNC) analysis were used to extract intrinsic networks and detect dysfunction among these networks. The clinical characteristics and FNC abnormalities were considered as features, and a support vector machine (SVM) model with five-fold cross-validation was applied to distinguish the subjects at an individual level. Dysfunctional connections within seven networks were observed, including default mode network (DMN), executive control network (ECN), salience network (SN), sensorimotor network (SMN), dorsal attention network (DAN), visual network (VN), and auditory network (AN). Compared with M-ieNSAIDs and HCs, M-eNSAIDs patients displayed reduced DMN-VN and SMN-VN, and enhanced VN-AN connections. Moreover, M-eNSAIDs patients showed increased FNC patterns within ECN, DAN and SN, relative to HCs. Higher ECN-SN connections than HCs were revealed in M-ieNSAIDs patients. Then, the SVM model demonstrated that the area under the curve, sensitivity and specificity were 0.93, 0.88 and 0.89, respectively. The widespread FNC impairment existing in the modulation of medical treatment, suggested FNC disruption as a biomarker for advancing the understanding of neurophysiological mechanisms and improving the decision-making of therapeutic strategy.